The effect of hirsutism on the quality of life of Indian women - K. C., Kiran; Gupta, Arushi; Gupta, Mohini (International Journal of Research in Dermatology, 2018)
Background: Quality of life is an individual perception of physical, psychological and social functioning. Hirsutism is excess male pattern hair growth in females. In women, hirsutism causes significant psychological and social problems. It impacts quality of life negatively. So, this study was undertaken to determine the quality of life of women with hirsutism using dermatology life quality index (DLQI). Methods: Hirsutism was assessed quantitatively by Ferriman-Gallwey score (F-G score) and qualitatively by self-administered questionnaires of DLQI. Other parameters such as age, occupation, co- morbidities, socio-economic status, marriage status, religion, educational status were assessed. Results: DLQI of 100 hirsute women, 12% had no effect, 34% had small effect, moderate effect in 37%, had very large effect in 17% and no patients had extremely large affect. Daily activity had highest mean DLQI followed by symptoms and feelings. The mean DLQI score of 100 hirsute women was 6.67±4.57. Mean DLQI score of hirsute women with polycystic ovarian syndrome (PCOS) was 9.96±5.62 which was greater than the patients without PCOS and it was statistically significant (p=0.03). DLQI score was not affected by severity of hirsutism, age, occupation, socio-economic status, marriage status, religion and educational status. Conclusions: Hirsutism had a moderate effect on the quality of life of Indian women. Impairment of quality of life was greater with the presence of PCOS. Daily activity of the Indian women was affected the most due to the presence of hirsutism.